2022
DOI: 10.57178/atestasi.v5i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism and Work Experience on Job Satisfaction and Auditor Performance

Abstract: This study aims to determine and analyze the impact of professionalism and work experience on auditors' job satisfaction and its implications for their performance at public accounting firms in Makassar. This research employs a survey method to collect data by distributing questionnaires and reviewing documentation. This study's population consisted of 50 auditors, but only 38 participants were sampled. Utilizing Smart PLS 3.0 Software, multiple linear regression analysis is used to analyze the data. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These emerging challenges could consequently hurt auditors' job satisfaction. Previous work found that low audit workload (Persellin et al, 2019), variable work experiences and higher professionalism (Badaruddin et al, 2022), less work–family conflict (Geroda & Puspitasari, 2017), and satisfying communications with supervisors (Pincus, 1986) lead to increased auditor job satisfaction. However, Jin et al (2022) interviews revealed a higher workload, higher audit risk, and lower communication efficiency associated with remote auditing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These emerging challenges could consequently hurt auditors' job satisfaction. Previous work found that low audit workload (Persellin et al, 2019), variable work experiences and higher professionalism (Badaruddin et al, 2022), less work–family conflict (Geroda & Puspitasari, 2017), and satisfying communications with supervisors (Pincus, 1986) lead to increased auditor job satisfaction. However, Jin et al (2022) interviews revealed a higher workload, higher audit risk, and lower communication efficiency associated with remote auditing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teaching experience is a significant individual component connected with teachers' professional development engagement (Badaruddin et al, 2022); this brought the topic of teaching experience more attention. According to Huberman (1989) and Steffy and Wolfe (2001), the participation patterns of teachers in professional development activities reveal unique ways as they go through their teaching careers.…”
Section: Experience and Job Satisfactionmentioning
confidence: 99%
“…To fulfill his responsibilities, an auditor must have a professional attitude and superior work skills, and the results can be seen from his performance. Financial statements are important information for auditors that is needed to determine whether the report is reasonable without exception (WTP) or reasonable with exception (WDP) (Badaruddin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%